The effect of microthread design on magnitude and distribution of stresses in bone: A three-dimensional finite element analysis - Golmohammadi, Shima (Dent Res J (Isfahan), 2018)
BACKGROUND: The researches regarding the influence of microthread design variables on the stress distribution in bone and a biomechanically optimal design for implant neck are limited. The aim of the present study is to compare the effect of different microthread designs on crestal bone stress. MATERIALS AND METHODS: Six implant models were constructed for three-dimensional finite element analysis including two thread profile (coarse and fine) with three different lengths of microthreaded neck (1 mm, 2 mm, and 3 mm). A load of 200 N was applied in two angulations (0° and 30°) relative to the long axis of the implant and the resultant maximum von Mises equivalent (EQV), compressive, tensile, and shear stresses were measured. RESULTS: Regardless of loading angle, the highest EQV stress was concentrated in the cortical bone around the implant model using a 1 mm neck of fine microthreads. Under axial loading, there was a negative correlation between the length of the microthreaded neck and stress level in both profiles. However, the same pattern was not observed for coarse microthreads under oblique loads. All types of measured stresses in all constructed models were increased with oblique loading. CONCLUSION: Peak stress levels in implant models varied with microthread profile and direction of loading. The microthread profile seemed more important than the length of the neck in reducing loading stresses exerted on the surrounding bone. Fine microthreads on a 3 mm implant neck showed consistently higher cortical bone stress than other models.